DETERMINACE VÝSLEDKŮ INCIDENČNÍ ANALÝZY TRHU S POTRAVINAMI - Petr David (Trendy v podnikání, 2015)
A number of authors has devoted to the measuring the distribution of the tax burden in the practice. In addition to the observed values they contribute to the diffusion of related phenomena and factors determining the tax incidence often due to a combination of quantitative and qualitative research. The chosen method of quantification of distribution of the tax burden is based on established models examining the tax incidence. It offers a clear calculation of the values without introducing confounding, complicated, and often distorting assumptions of general equilibrium models. However the results need to be understood in the context of the given situation of the analysed economies and to admit their determination by other factors. This study deals with evaluation of appropriateness of the inclusion of the factors determining the input data of incidence analysis. Incidence analysis is realized on the case of reduced value added tax rate imposed on foodstuff in the Czech Republic in 2013. This analysis uses the consumer price indices CPI by Classification of Individual Consumption by Purpose COICOP obtained from Czech Statistical Office. Examining determinants are core inflation and seasonal effect. The initial average value of distribution of the tax burden at a reduced value added tax rate growth in the Czech Republic in 2013 is 55%, which means that more than one half of the additional tax burden is borne by consumers. The remaining part of increased tax burden is borne by sellers. In this research was found that inclusion of additional effects on consumer price indices changes results of shifting the tax burden by only 2%. So the results of the research show the negligible effect of including those factors in performed calculations.